Posted by **Andrew** on Monday, January 30, 2012 at 9:35pm.

5(-3x - 2) - (x - 3) = -4(4x + 5) + 13

Answer

Multiply factors.

-15x - 10 - x + 3 = -16x - 20 +13

Group like terms.

-16x - 7 = -16x - 7

Add 16x + 7 to both sides and write the equation as follows

0 = 0

- Math -
**PsyDAG**, Tuesday, January 31, 2012 at 11:36pm
Looks good.

## Answer This Question

## Related Questions

- algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...
- Math - I sent this in a little while back but the file got corrupted and I have ...
- Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...
- Intermediate Algebra - Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^...
- algebra - x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem ...
- math - The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct? [(2x...
- math - please help - Find the HCF and LCM of: 1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - ...
- Pre-Calculus - Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1...
- Math - Which of the following expressions is equivalent to (-2x^5 y^2)^4 A. -16x...
- math - Find the HCF and LCM of: 1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - 8x^3 - 16x^4...

More Related Questions